Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.55940/medphar20225
|View full text |Cite
|
Sign up to set email alerts
|

Perception, knowledge, and attitude of solar radiation diseases and use of sunscreen among Al Zawia Medical University Students in Libya

Abstract: Background. The patient needs from the doctor things such as interest visual contact, empathy, of this and the most important thing is good treatment and diagnosis, However, the patient usually did not receive the level of requirement from their doctors. Objective. Evaluate the expected requirement regarding family history and other doctors and care providers, end find out what the patient expected from family physicians in multi- hospitals and health care centers in the middle east. Methods. We use a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Table 1 shows that females (59.6%) were more prominent than males (40.4%) and the main age group (43.4%) were in (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) years with mean age of (32 ± 9) years. Regarding to job category; the surgeons, assistance surgeons, nurses, and laboratory technicians were represented in (23.1%) for each one and the dentists were only found in (7.7%), (58.5%) were worked in ward, (33.8%) in emergency room, and only (7.7%) in outpatients department.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows that females (59.6%) were more prominent than males (40.4%) and the main age group (43.4%) were in (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) years with mean age of (32 ± 9) years. Regarding to job category; the surgeons, assistance surgeons, nurses, and laboratory technicians were represented in (23.1%) for each one and the dentists were only found in (7.7%), (58.5%) were worked in ward, (33.8%) in emergency room, and only (7.7%) in outpatients department.…”
Section: Resultsmentioning
confidence: 99%
“…Siddique et al [39] in their study concluded prevalence of NSI found in 94% of the subjects which is very high that may be due to reporting of the injuries by HCWs.…”
Section: Prevalence Of Nsis Among Hcwsmentioning
confidence: 87%
“…They were collected from the College of Pharmacy's Animal House at Baghdad University. They were housed in polypropylene plastic cages (three animals per cage) under carefully controlled circumstances (temperature, humidity, and light/dark cycles) (7). The animals were given unlimited access to commercial pellet diet and water.…”
Section: Methodsmentioning
confidence: 99%
“…Groups I-Controls: Rats were administered a single intraperitoneal injection (IP) with normal saline (NS (0.5 ml / 250 g body weight) and then the animals were euthanized with anesthetic ether 24 hours after NS giving (such as ketamine) (2) . II-Nefopam -treated animals: Rats were injected with a one toxic amount of IPP (40 mg/kg) Nefopam and then the experimental rats were sacrificed with anesthetic ether 24 hours after drug administration (7,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation